New soliton properties to the ill-posed Boussinesq equation arising in nonlinear physical science - Sulaiman, Tukur Abdulkadir B; Aşkın, Muzaffer; Duran, Serbay (My University, 2017)
In manuscript, with the help of the Wolfram Mathematica 9, we employ themodified exponential function method in obtaining some new soliton solutions tothe ill-posed Boussinesq equation arising in nonlinear media. Results obtainedwith use of technique, and also, surfaces for soliton solutions are given. We alsoplot the 3D and 2D of each solution obtained in this study by using the sameprogram in the Wolfram Mathematica 9.
Keywords: Fizik; Uygulamalı; Matematik